AID EFFECTIVENESS AND LESSONS LEARNT AMONG TEENAGE MOTHERS IN BIDIBIDI REFUGEE SETTLEMENT - Nsamba, Ahumedi (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
Established in 2016 and receiving over 285,000 refugees, Bidibidi was marked as the largest refugee settlement in Uganda by 2018. The outbreak of Covid-19 generated a lot of aid for the refugees in the settlement but worsened the situation in the post pandemic period, especially among teenage mothers. Building on scholarship about aid and humanitarian work, this study advances the insights of the lived experiences and lessons learnt by teenage refugee mothers in the post-Covid-19 Bidibidi refugee settlement of north western Uganda. This study employed a qualitative method of research undertaken using snowball sampling to obtain interviews from 10 teenage mothers and 2 key informants from the UNHCR and the OPM respectively. The results of the study established a number of impacts ranging from economic for example; loss of property due to the increased theft cases, psychological effects including the fear of men from the girls to the extent that they have to move in groups to avoid rapists, and social impacts for example the closure of Rabita events that were aimed at helping each other to recover the property lost during the war. The study identified inadequate resources and limited timeline as key issues that bring about failed effectiveness and later compromise sustainability of aid among teenage mothers in the settlement. Increased attention on monitoring and evaluation from the office of the prime minister (OPM) and the UNHCR would be paramount to avoid duplication and project overlaps.